Fintech in sub-Saharan Africa - Njuguna S. Ndung'u (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
This paper traces the development of fintech in sub-Saharan Africa, its evolution over time, and the unfolding benefits attained at each stage of its adoption and market evolution. From the onset, fintechs have revolutionized retail electronic payment systems-a revolution that has evolved into a technological platform to manage micro-savers' accounts, virtual savings and credit systems, public financial management, and cross-border remittances, and has led to the adoption of new monetary policy frameworks. The uptake of fintech products has led to increased financial inclusion for underserved and unserved populations, improvement of welfare, and the efficient and cost-effective provision of services across all sectors of the economy. The paper also outlines the challenges that persist and need to be addressed to allow the rapid uptake of fintech products and solutions in sub-Saharan Africa. The paper concludes that the fourth Industrial Revolution, driven by fintech, has the potential to propel the continent to higher levels of savings, investments, employment, and inclusive growth, provided an appropriate legal and regulatory framework is put in place and resources are channelled for sufficient infrastructural development.
Keywords: G21; G23; O14; O55; 330; fintech; financial inclusion; micro-savers; technology; sub-Saharan Africa